Dapagliflozin Attenuates Renal Tubulointerstitial Fibrosis Associated With Type 1 Diabetes by Regulating STAT1/TGFβ1 Signaling - Huang, Fengjuan; Zhao, Yanyan; Wang, Qingzhu; Hillebrands, Jan-Luuk; Born, Jacob van den; Ji, Linlin; An, Tingting; Qin, Guijun (Frontiers in Endocrinology, 2019)
Tubulointerstitial fibrosis (TIF) plays an important role in the progression of renal fibrosis in diabetic nephropathy (DN). Accumulating evidence supports a crucial inhibitory effect of dapagliflozin, a SGLT2 inhibitor, on TIF, but the underlying mechanisms remain largely unknown. This study aimed to shed light on the efficacy of dapagliflozin in reducing TIF as well as its possible impact on renal function. TIF in human kidney biopsies obtained from patients with DN was quantified by histopathological staining. In vitro, HK-2 cells were incubated in high glucose with dapagliflozin or fludarabine, and epithelial-mesenchymal transition (EMT) was determined. In vivo experiments were performed in streptozotocin (STZ)-induced type 1 diabetic mice treated with dapagliflozin by gavage for 16 weeks, after which specific functional characteristics and TIF were analyzed. In both DN patients and diabetic mice, fibronectin and Col IV, as well as STAT1 protein in the kidneys were increased as compared with controls. Dapagliflozin significantly decreased blood glucose, and renal STAT1 and TGF-β1 expression in mice. Furthermore, dapagliflozin improved renal function, and attenuated diabetes-induced TIF. In HK-2 cells, dapagliflozin and fludarabine directly decreased aberrant STAT1 expression and reversed high glucose-induced downregulation of E-cadherin and α-SMA induction. Thus, the results demonstrate that dapagliflozin not only improves hyperglycemia but also slows down the progression of diabetes-associated renal TIF by improving hyperglycemia-induced activation of the STAT1/TGF-β1 pathway.